A Sociological Theory of Value: Georg Simmel's Sociological Relationism - Cantó Milà, Natàlia (transcript, 2015)
In this book, Natàlia Cantó Milà elaborates on Georg Simmel's relational approach to a theory of value, pointing at the heuristic possibilities that this approach offers to modern sociology and to a sociology of modernity. She does so by focusing on the theory of value Simmel developed in his »The Philosophy of Money«, delivering an alternative reading of this book that views its theory of value as its main axial point. Simmel's theory of value is depicted by Cantó Milà as including an intrinsically sociological aspect, since economic as well as moral, ethic and aesthetic values are conceived as resulting from human relations.